Scripts of Emily Post - Post, Emily, 1873-1960.
Transcripts of weekly radio talks on etiquette.
Author and radio commentator. Full name: Emily Price Post (Mrs. Edwin M. Post).
Collection material in English.
Keywords: Etiquette; Authors; Radio journalists